Mobilidades populacionais em municípios de pequeno porte receptores de grandes empreendimentos: estudo de caso na região de Conceição do Mato Dentro MG, 2010-2012 - Laura Ladeira Loes (2015)
The main objective of this dissertation are to study the types of population movements migration, commuting, and temporary mobility their relationships, and the volumes and flows occurring in small municipalities receptors to a great enterprise. This research interest arose from the substantial volume of mobility pointed out in several Environmental Impact Studies. Added to this, the dissertation analyzes the difficulty of defining each of these movements and the inconsistency of information on workers who make a temporary move without determining residence. The dissertation discusses the types of mobility, their determinants and conceptual applications, and reviews several studies that have focused on the subject of mobility in large enterprises. As a case study, this dissertation uses the Conceição do Mato Dentro region in Minas Gerais, which in 2010 was the location for the installation of the Minas-Rio Mining Project. Socioeconomic profiles of these movements are analyzed, assessing their similarities and differences, especially for the group of workers who performed mobility during the installation phase. In this dissertation data was obtained from a survey published by the entrepreneur and information available in the Census 2010. Census data favors the descriptive analysis of the socioeconomic profiles, calculation of Net Migration and Rate Net Migration, and changes in commuting and building a matrix origin. Moreover, socioeconomic information are examined through combinations of categories of population mobility only migrants, only commuting, and migrants and commuters by description and by creating profiles for each of these groups using Principal Component Analysis (PCA). The results show that, in general, the movements have different socioeconomic profiles, especially if consider gender, age, marital status, and education. It is concluded that the evaluation of the types of mobility carried out in small municipalities, and large enterprise receptors, contributes to knowledge and analysis of mobile populations which have been until now poorly studied in Brazil.